1990
DOI: 10.1128/jcm.28.9.1982-1987.1990
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a repetitive DNA sequence from Bordetella pertussis and its application to the diagnosis of pertussis using the polymerase chain reaction

Abstract: A tandemly repeated 1,046-base-pair (bp) ClaI DNA fragment from Bordetella pertussis was cloned into Escherichia coli by using the vector pUC19. This fragment, when isolated, hybridized strongly to DNA from all 100 clinical isolates of B. pertussis tested. It was shown to have homology to single-copy sequences in Bordetella bronchiseptica but not Bordetella parapertussis and did not hybridize to lysate blots of a wide range of other bacteria, including members of the closely related genera Pasteurella, Alcalig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(79 citation statements)
references
References 20 publications
5
71
1
Order By: Relevance
“…Laboratory tests were performed at the Vaccine Bio Institute (VBI) of The Catholic University of Korea. It is determined as the criteria for laboratory-confirmed pertussis case when the subjects is applicable to one of the following criteria: 1) positive result of B. pertussis on culture of nasopharyngeal aspirates (NPA) or swab; this sample was collected and cultured on Regan-Lowe culture medium at 37°C for more than 1 week; 2) positive result of B. pertussis in PCR or real-time PCR (RT-PCR) of NPA or swab; PCR was done by the method Glare et al reported (16), and RT-PCR was done by modified method of Reischl U. Colleagues manual (17); 3) positive serology which defined as pertussis toxin (PT) antibody in a single serum sample that was higher than cut-off value (24 EU/mL) of enzymelinked immunosorbent assay (ELISA) kit (IBL, Hamburg, Germany) or a 4-fold increased change in anti-PT antibody between acute-phase and convalescent-phase serum.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Laboratory tests were performed at the Vaccine Bio Institute (VBI) of The Catholic University of Korea. It is determined as the criteria for laboratory-confirmed pertussis case when the subjects is applicable to one of the following criteria: 1) positive result of B. pertussis on culture of nasopharyngeal aspirates (NPA) or swab; this sample was collected and cultured on Regan-Lowe culture medium at 37°C for more than 1 week; 2) positive result of B. pertussis in PCR or real-time PCR (RT-PCR) of NPA or swab; PCR was done by the method Glare et al reported (16), and RT-PCR was done by modified method of Reischl U. Colleagues manual (17); 3) positive serology which defined as pertussis toxin (PT) antibody in a single serum sample that was higher than cut-off value (24 EU/mL) of enzymelinked immunosorbent assay (ELISA) kit (IBL, Hamburg, Germany) or a 4-fold increased change in anti-PT antibody between acute-phase and convalescent-phase serum.…”
Section: Data Sourcesmentioning
confidence: 99%
“…(Eisenach etai. 1990), Bordetella pertussis (Glare et al. 1990), Rhodomicrobium vannielli (Russell and Mann, 1986), Agrobacterium spp, and Rhizobium spp.…”
Section: Introductionmentioning
confidence: 99%
“…A direct nucleic acid extraction was performed from the nasopharyngeal samples using the High Pure Template Preparation Kit (Roche Applied Science, Mannheim, Germany) following the manufacturer's instructions, and pertussis status was confirmed by PCR. Thus, both 191 bp of the ptxA gene and 145 bp of the IS418 were amplified using primers described elsewhere [16,17] . To confirm the correctness of the amplifications the PCR products were recovered, purified (SpinPrepTM Gel DNA Kit, San Diego, USA) and sequenced (Macrogen, Seoul, Korea).…”
Section: Clinical Diagnosismentioning
confidence: 99%